Differential brain activation and network connectivity in social interactions presence and absence of physical contact - Jinhe Zhai; Xinyi Zhang; Xinxin Wang; Zihan Xu; Xueke Yao; Yuying Zhang; Lili Fan; Lijie Wu; Jia Wang (Communications Biology)
Abstract Comparative studies of social interaction in the presence of physical contact (SIPPC) and social interaction in absence of physical contact (SIAPC) enhance our understanding of the neurophysiological mechanisms underlying these activities. We analyzed comparatively the effects of SIPPC and SIAPC on c-fos expression across 100 brain regions in mice, and found that SIPPC activated a broader range of brain regions, particularly those associated with emotion and reward. Subsequent observations of brain activity coordination and network construction highlighted the critical roles of the infralimbic cortex (IL), lateral septal nucleus intermediate part (LSI), and agranular insular cortex ventral part (AIV) in SIPPC. Additionally, we demonstrated through chemogenetic techniques that inhibiting the activity of AIV, LSI brain regions, or AIV-LSI circuit significantly reduces the tactile contact behavior of mice during SIPPC. To sum up, our findings elucidate the similarities and differences in brain activity and network connectivity between SIPPC and SIAPC, while identifying specific brain regions and neural circuit that may mediate tactile contact in social interaction.